A Comparative Review on Current and Future Drug Targets Against Bacteria & Malaria - Rout, Usha K.; Sanket, A.S.; Sisodia, Brijesh S.; Mohapatra, Pradyumna K.; Pati, Sanghamitra; Kant, Rajni; Dwivedi, Gaurav R. (Current Drug Targets, 2020)
Long before the discovery of drugs like ‘antibiotic and anti-parasitic drugs’, the infectious diseases caused by pathogenic bacteria and parasites remain as one of the major causes of morbidity and mortality in developing and underdeveloped countries. The phenomenon by which the organism exerts resistance against two or more structurally unrelated drugs is called multidrug resistance (MDR) and its emergence has further complicated the treatment scenario of infectious diseases. Resistance towards the available set of treatment options and poor pipeline of novel drug development puts an alarming situation. A universal goal in the post-genomic era is to identify novel targets/drugs for various life-threatening diseases caused by such pathogens. This review is conceptualized in the backdrop of drug resistance in two major pathogens i.e. “Pseudomonas aeruginosa” and “Plasmodium falciparum”. In this review, the available targets and key mechanisms of resistance of these pathogens have been discussed in detail. An attempt has also been made to analyze the common drug targets of bacteria and malaria parasite to overcome the current drug resistance scenario. The solution is also hypothesized in terms of a present pipeline of drugs and efforts made by scientific community.
Keywords: drug resistance